A 2D test setup for scaled real-time hybrid tests of dynamic ice-structure interaction - Hammer, T.C. (author); van Beek, C. (author); Koning, J.R.A. (author); Hendrikse, H. (author) (2021)
With the ongoing development of offshore wind in cold regions where the foundations are exposed to sea ice, there is a strong need for data to validate the numerically predicted dynamic interaction between ice and structure used for design. Full-scale data is non-existent and only a limited number of experimental campaigns in ice tanks have been conducted for this specific problem. When compared to traditional structures subjected to sea ice loading like lighthouses and oil and gas platforms, the motion of the turbines at the ice action point is both in line with the ice drift direction but also significantly across due to the interaction of the turbine with the wind. Furthermore, the structure being slender overall and having a large top mass results in a very particular set of modes of oscillation where at least both the first and second global bending mode are expected to interact with the ice. To capture this complexity, a real-time hybrid test setup has been designed for basin tests in the SHIVER project and is presented in this paper. The setup uses two integrated linear actuators to control the motion of a rigid pile in two dimensions. Loads at the ice-action point are measured and used in a numerical model where these are combined with virtual loads, for example wind loading, to determine the response of the structure which is then applied in the physical setup by the actuators. The system allows to test a wide range of combinations of structural stiffness, mass, and damping, including structural properties typically associated with the relevant modes of oscillation of offshore wind turbines. Offshore Engineering EMSD CE&G EMSD EEMCS Project engineers1